A LADM-based temporal cadastral information system for modelling of easement rights - A case study of Turkey - Polat, Z. A.; Alkan, M.; van Oosterom, P. J. M.; Lemmen, C. H. J. (TAYLOR & FRANCIS LTD, 2020)
Type people to land relations are dynamic and, as a consequence, the nature of land title and cadastral data is of a dynamic nature. Land title and cadastral data are core components for a lot of property applications (e.g. taxation, valuation, mortgage). Those applications require up to date, complete and reliable data - including temporal data as in use in application forms and transactions. In this paper, the modelling of Rights, Restrictions and Responsibilities (RRR) is discussed with a focus on the modelling of easement rights in a case study in Turkey. Functional requirements with respect to the characteristics of easement rights are investigated based upon interviews with professional experts in the public and private sector. Then a prototype model was built based on a simple implementation of the Land Administration Domain Model (LADM) RRR classes and by conforming to the national cadastral data management standards related to land registration systems. This new proposed model includes temporal cadastral attributes related to easements. This is materialised in the 'Administrative Package' and illustrated in the Turkey LADM country profile. We show that the LADM can be used to describe for the time dimension of cadastral information in Turkey, but that there are semantic differences, similarities and mismatches of classes and attributes between the LADM and the cadastral information system in Turkey. Proposed LADM-based model for the time dimension of cadastral information will be of immense advantage to land administrators, the governments and land users in Turkey.
Keywords: Temporal LTC data; ISO 19152 LADM; Easement rights; Land registry; Cadastre; Turkey Country profile; ADMINISTRATION DOMAIN MODEL; LAND; Engineering; Geology; Remote Sensing